ANALYSIS OF TRAFFIC LIGHTS AND ROUNDABOUTS, A CONTINUUM APPROACH - NOVTIAR , CHANDRA
In this thesis traffic ow problem is studied as a continuum. We use a hyperbolic diferential equation, known as traffic equation with trafic density as the continuous variable. The orde Godunov method is applied to simulate exact solution of Riemann problem for various conditions, such as the growth of queue length behind an intersection, and also to get the clearance time for an intersection with traffic light or roundabout. The resulting numerical code is used to find a balance between traffic light and roundabout. In this thesis ITS (Intelligent Transportation System) method is implemented for comparison.